Quasiadiabatic electron transport in room temperature nanoelectronic devices induced by hot-phonon bottleneck - Qianchun Weng (Nature Portfolio, 2021)
Minimizing the energy dissipation is usually sought by eliminating phonon-emission process. Here, the authors find a different approach for facilitating energy transmission at room temperature that electrons exert diffusive but quasiadiabatic transport, free from substantial energy loss.